Learning Outcomes on Plant Structure and Function Through the Demonstration Method: Hasil Belajar Struktur dan Fungsi Tumbuhan Melalui Metode Demonstrasi - Intihana, Muhklisatun (Indonesian Journal of Innovation Studies, 2025)
Background: Learning the structure and function of plant parts in elementary school often requires concrete instructional approaches to support students who are still in the concrete operational stage. Specific background: At SDN 2 Srisawahan, Grade V students demonstrated low achievement on this topic when taught through conventional explanations. Knowledge gap: Limited research documents how demonstration-based instruction specifically supports learning outcomes in the plant structure and function material. Aim: This study examines student learning outcomes on the topic of plant structure and function when taught through the demonstration method. Results: Using two cycles of Classroom Action Research with 13 students, mastery increased from 38.5% in cycle I to 84.6% in cycle II, indicating clearer understanding and higher task completion after engaging in direct observation and guided demonstrations. Novelty: The study offers classroom-based evidence showing that demonstration activities help students connect concrete experiences with conceptual descriptions of plant parts and their roles. Implications: These findings suggest that demonstration can serve as a practical instructional approach for teachers to strengthen learning outcomes in science topics requiring visualization and hands-on engagement. Highlights Demonstration activities helped students understand plant parts and their functions through direct observation. Learning outcomes showed substantial improvement after structured demonstrations across two cycles. Students participated more actively and expressed plant-related concepts with greater clarity. Keywords Plant Structure And Function, Demonstration Method, Learning Outcomes, Elementary Science, Classroom Action Research